A design of compound tailored illumination by a total-internal-reflection lens for machine vision. (December 2021) - Sun, X; Kong, LB; Zhou, PY; Xu, M
In machine vision systems, the objectives to be detected, such as circuit boards, may be composed of many different materials and shapes, which can lead to highlights, shadows and error information in captured images under traditional uniform illumination. A lighting system that generates tailored irradiance in different regions in machine vision is needed. This paper proposes a design method for an LED lens and obtains special total-internal-reflection (TIR) lenses that generate tailored illumination, which can adapt to the reflectance and shape of a target. Differential-algebraic equations (DAEs) based on the conservation of flux are established to ensure the uniform illumination on the targets, nonlinear equations based on the edge-ray principle are employed to generate the spots with tailored shapes and the numerical solutions can be fitted into the proposed lenses. Six different tailored faculae are generated to verify the proposed method. The results show that the uniformity of tailored facula can exceed 87%, and the light efficiency can exceed 85%. In particular, the contrast of the irradiance among different regions can be adjusted by the boundary conditions; thus, the proposed method can satisfy the complex demand for machine vision and be applied to improve vision detection systems in production lines.